A class of promising fuel cell performance : International status on the application of nanofluids for thermal management systems - Nurhanis Sofiah, Abd Ghafar; Pasupuleti, Jagadeesh; Samykano, Mahendran; Pandey, Adarsh Kumar; Rajamony, Reji Kumar; Nur Fatin, Sulaiman; Zatil Amali, Che Ramli (Elsevier Ltd, 2024)
Fuel cell technologies are developed due to their positive impact on the environment and their ability to empower sustainable energy compared to other power generators. The operating temperature of fuel cells influences the maximum capacity of the devices, with higher heat generation resulting in a lower theoretical maximum voltage and affecting the system's efficiency. The utilization of nanofluid systems in this kind of energy-related application is employed at lower costs but with higher efficiency. This review article investigates the recent development of nanofluids for the thermal management system of fuel cell technologies to enhance sustainable energy in the future. Nanofluids serve as coolants and create excitement among researchers due to their excellent behavior in thermal conductivity. This article, therefore, reviews the cooling approaches that have been commercialized for fuel cell devices and reports recent progress in the thermal management system and the employment of nanofluids in different types of fuel cell technologies. Important properties of nanofluids are critically discussed, and recent case studies (2018–2023) are recorded to provide a comprehensive understanding to the readers. Finally, the advantages and disadvantages of nanofluids as coolants for fuel cell operation are discussed. It is reported that these nano-enhanced coolants provide improvements to fuel cell technology in terms of smaller system dimensions, eliminating deionizing components, and exhibiting higher heat transfer behavior compared to conventional coolants. Progressively move towards cleaner energy, including nanofluids into fuel cell design offers a viable way to achieve higher energy efficiency, less environmental impact, and a more sustainable future.